External Field‐Assisted Metal–Air Batteries: Mechanisms, Progress, and Prospects - Ruien Cao; Limin Liu; Wei Yu; Shujiang Ding (SusMat)
ABSTRACT Metal–air batteries are an appealing option for energy storage, boasting a high energy density and environmental sustainability. Researchers focus on the catalyst design to solve the problem of sluggish cathode reaction kinetic. However, in some cases, where thermodynamic regulation is required, the role of catalysts is limited. Based on catalysts changing reaction kinetics, external fields can change the thermodynamic parameters of the reaction, further reduce overpotential, and accelerate the reaction rate. By selecting appropriate external fields and adjusting controllable variables, greater flexibility and potential are provided for reaction control. This paper reviews the basic principles by which several external fields influence metal–air batteries. Additionally, some design strategies of photoelectrode materials, the similarities and differences of different magnetic field effects, and some research progress of the ultrasonic field, stress field, and microwave field are systematically summarized. Multifield coupling can also interact and produce additive effects. Furthermore, introducing external fields will also bring about the problem of aggravated side reactions. This paper proposes some research methods to explore the specific reaction mechanism of external field assistance in more depth. The primary objective is to furnish theoretical direction for enhancing the performance of external field‐supported metal–air batteries, thereby advancing their development.